2년 이상 저농도 아트로핀 점안한 소아 환자에서 근시 진행과 안축장 변화 - Hye Won Park (검안 및 콘택트렌즈 학회지, 24(2), 2025)
목적: 소아 근시 환자에서 2년 이상 저농도 아트로핀 점안이 근시 진행과 안축장 변화에 미치는 영향을 알아보고자 한다. 대상과 방법: 의무기록 후향적 분석 연구로 2018년 1월부터 2022년 6월까지 본원에 내원하여 안축장을 측정한 근시 환자를 대상으로하였다. 아트로핀 사용군(106명)과 아트로핀 사용하지 않은 대조군(38명)의 저농도 아트로핀 점안 전, 후 2년간 구면렌즈대응치와 안축장 변화를 분석하였다. 결과: 2년간 안축장 변화의 중위수는 아트로핀 점안군에서 우안은 0.72 mm, 좌안은 0.71 mm로 나타났고, 대조군에서 우안은 0.48 mm, 좌안은 0.55 mm로 나타났으나 두 군 간 유의미한 차이를 보이지 않았다(OD: p-value = 0.136; OS: p-value = 0.155). 2년간 구면렌즈대응치 변화의 중위수는 아트로핀 점안군에서 양안 1.63 D, 대조군에서 양안 2.25 D로 두 군 간 유의미한 차이를 보였다(OD: p-value = 0.009; OS: p-value < 0.001). 결론: 소아 및 청소년 환자를 대상으로 2년 이상의 저농도 아트로핀 점안은 구면렌즈대응치 변화를 지연시키는 효과가 있는 것으로생각된다. Purpose: This study investigated the effects of low-dose atropine eye drops on myopia progression and axial length changes in pediatric patients with myopia for > 2 years. Methods: We retrospectively analyzed the medical records of patients with myopia who visited our hospital and underwent axial length measurement between January 2018 and June 2022. This study compared the outcomes of the atropine (106 patients) and control (38 patients) groups. Changes in spherical equivalent (SE) and axial length were analyzed over 2 years before and after using low-dose atropine eye drops. Results: The median change in axial length was 0.72 mm for the right eye (OD) and 0.71 mm for the left eye (OS) in the atropine group, whereas the control group showed a median change of 0.48 mm (OD) and 0.55 mm (OS). However, there was no significant difference between both groups (OD: p = 0.136; OS: p = 0.155). The median change in SE was 1.63 diopters (D) and 2.25 D in the atropine and control groups, respectively, with a significant difference between both groups (OD: p = 0.009; OS: p < 0.001) for 2 years. Conclusions: In pediatric and adolescent patients, the use of low-dose atropine eye drops for > 2 years appeared to delay changes in the SE, suggesting its potential effectiveness in slowing myopia progression. KCI Citation Count: 0